Penetapan Kadar Rhodamin B Pada Bumbu Tabur Dengan Metode KLT Dan KCKT - Munthe, Ariska; Daulay, Anny Sartika; Ridwanto, Ridwanto; Pulungan , Ainil Fithri (Journal of Pharmaceutical and Sciences, 2025)
Rhodamine B is a colouring substance in the form of green or reddish-purple crystals, which are odourless and in the form of a bright red solution (fluorescent). Rhodamin B is a colouring substance that can only be used in the textile, paint, paper, or clothing industries, so it cannot be added to food. Rhodamine B is often used as a coloring agent in paper and textiles. This substance is the most dangerous; if consumed, it can cause problems with liver function and liver cancer. The stages of this research include a sample solution, making Rhodamin B standard stock solution, and making a mobile phase. Examination of qualitative analysis using thin layer chromatography and determination of Rhodamine B levels in seasoning performance liquid chromatography method. The results of the research showed that in the qualitative examination, there were two samples containing Rhodamin B. Rhodamin B levels were determined by determining the retention time and calculating Rhodamin B levels using the high-performance liquid chromatography method. The result of deciding Rhodamine B levels in the two samples containing Rhodamin B was sample A; 2,8915 mcg/g  ,sampel B ; 19,6702 mcg/g  Mcg/g. Then, the highest levels of Rhodamin B are found in sample B.